Cytokinin biosynthesis in cyanobacteria: Insights for crop improvement - Uniyal, Shashi; Bhandari, Munni; Singh, Preeti; Singh, Rahul Kunwar; Tiwari, Shree Prakash (Frontiers in Genetics, 2022)
Cytokinins, a type of phytohormones that induce division of cytoplasm, have considerable value in agriculture due to their influences on several physiological processes of plants such as morphogenesis, development of chloroplast, seed dormancy, leaf senescence, etc. Previously, it was assumed that plants obtain cytokinin from the soil produced by microbes as these hormones were first discovered in soil-inhabiting bacteria i.e., Agrobacterium tumefaciens. Later, the cytokinin biosynthesis gene, i.e., ipt gene, has been reported in plants too. Though plants synthesize cytokinins, several studies have reported that the exogenous application of cytokinins has numerous beneficial effects including the acceleration of plant growth and boosting economic yield. Cyanobacteria may be employed in the soil not only as the source of cytokinins but also as the source of other plant growth-promoting metabolites. These organisms biosynthesize the cytokinins using the enzyme isopentenyl transferases (IPTs) in a fashion similar to the plants; however, there are few differences in the biosynthesis mechanism of cytokinins in cyanobacteria and plants. Cytokinins are important for the establishment of interaction between plants and cyanobacteria as evidenced by gene knockout experiments. These hormones are also helpful in alleviating the adverse effects of abiotic stresses on plant development. Cyanobacterial supplements in the field result in the induction of adventitious roots and shoots on petiolar as well as internodal segments. The leaf, root, and stem explants of certain plants exhibited successful regeneration when treated with cyanobacterial extract/cell suspension. These successful regeneration practices mark the way of cyanobacterial deployment in the field as a great move toward the goal of sustainable agriculture.